Teacher Perspectives on Student Placement in University EFL Programs - McMillan, Brian; Joyce, Paul (Journal of NELTA, 2012)
In many language programs, students are placed in streamed, relatively homogeneous classes according to their proficiency in the target language. However, proponents of mixed-ability classes believe that through forming mixed-ability groups lower-proficiency learners feel less stigmatized, and that both higher- and lower-proficiency learners benefit from peer tutoring. This paper reports on the results from a survey that explored the perceptions of 31 EFL teachers at four Japanese universities regarding streamed and mixedability first-year EFL classes. Most teacher-participants expressed a preference for teaching streamed classes, citing advantages related to the effectiveness of instruction, appropriateness of materials, student motivation, and the quality of learner-learner interaction. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6131 NELTA 2011; 16(1-2): 70-81